2015
DOI: 10.2472/jsms.64.880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Fatigue Properties of Ti-6Al-4V Alloy with Harmonic Structure in 4-Points Bending

Abstract: Titanium alloy (Ti-6Al-4V) having a bimodal "harmonic structure", which consists of the coarse-grained structure surrounded by the network structure with fine grains, was fabricated by mechanical milling (MM) and spark plasma sintering (SPS) to achieve high strength and good plasticity. The microstructure of the MM-processed powder and the sintered compacts were characterized using a micro-Vickers hardness tester, scanning electron microscope (SEM) and an electron backscatter diffraction technique (EBSD). Harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…Fig. 1 shows the image quality (IQ) maps obtained by EBSD for the (a) IP and (b) Harmonic series [14]. The IP series has a coarse acicular microstructure, whereas the Harmonic series two different microstructures; fine-grained and coarsegrained structures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 1 shows the image quality (IQ) maps obtained by EBSD for the (a) IP and (b) Harmonic series [14]. The IP series has a coarse acicular microstructure, whereas the Harmonic series two different microstructures; fine-grained and coarsegrained structures.…”
Section: Methodsmentioning
confidence: 99%
“…The author's group [7][8][9][10][11][12][13] has developed an exquisite microstructural design, called "harmonic structure", which consists of coarse-grained structure surrounded by a network structure of fine grains. In the previous studies, metallic materials with harmonic structure, such as pure copper [7], stainless steel [8][9][10], Co-Cr-Mo alloy [11], commercially pure titanium [12] and Ti-6Al-4V alloy [13,14] exhibited high strength and high ductility compared to their homogeneous counterparts. The authors have focused on the fatigue properties of the Ti-6Al-4V alloy with harmonic structure and reported that a fatigue crack was initiated from the coarse-grained structure in the harmonic structure in 4-points bending [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a homogeneous fine-grained structure formed by severe plastic deformation generally leads to a decrease in the ductility of metallic materials [3][4][5][6][7][8] due to the initiation of plastic instability in the early stage. Therefore, various microstructural designs have been proposed to improve both the strength and ductility of these materials [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The disk-shaped specimens that had undergone each treatment were machined to the configuration shown in Figure 2, by precision cutting and polishing using emery paper (#120), to carry out four-point bending fatigue tests [7]. Fatigue tests were performed at room temperature in air, under a stress ratio of 0.1 and a stress cycling frequency of 10 Hz.…”
Section: Fatigue Tests Under Four-point Bendingmentioning
confidence: 99%